2022
DOI: 10.3390/s22218511
|View full text |Cite
|
Sign up to set email alerts
|

Passive Sonar Target Identification Using Multiple-Measurement Sparse Bayesian Learning

Abstract: Accurate estimation of the frequency component is an important issue to identify and track marine objects (e.g., surface ship, submarine, etc.). In general, a passive sonar system consists of a sensor array, and each sensor receives data that have common information of the target signal. In this paper, we consider multiple-measurement sparse Bayesian learning (MM-SBL), which reconstructs sparse solutions in a linear system using Bayesian frameworks, to detect the common frequency components received by each se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Currently, these efforts towards direction finding can be roughly grouped into two categories, i.e., subspace technologies [5][6][7][8] and sparse signal recovery (SSR) attempts [9][10][11][12][13]. The former are represented by the multiple signal classification (MUSIC) algorithm [5] and the estimation of signal parameters via rotational invariance techniques (ESPRIT) algorithm [6], officially opening the era of super-resolution direction finding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, these efforts towards direction finding can be roughly grouped into two categories, i.e., subspace technologies [5][6][7][8] and sparse signal recovery (SSR) attempts [9][10][11][12][13]. The former are represented by the multiple signal classification (MUSIC) algorithm [5] and the estimation of signal parameters via rotational invariance techniques (ESPRIT) algorithm [6], officially opening the era of super-resolution direction finding.…”
Section: Introductionmentioning
confidence: 99%
“…Motivated by the potential spatial sparsity of the targets, the SSR perspective based on the principle of Compressed Sensing (CS) [14,15] came into being to solve the above problem. Subsequently, a set of sparsity-aware estimators are structured, including convex optimization attempts [9][10][11] and sparse Bayesian learning (SBL) efforts [12,13]. Simultaneously, plenty of research results have shown that this not only improves the estimation accuracy under the conditions of undesirable SNR and snapshots, but also enhances the robustness to coherent sources [16].…”
Section: Introductionmentioning
confidence: 99%